## Solving the Equation (a + 28) = 2a

This article will guide you through the process of solving the equation (a + 28) = 2a. Let's break it down step-by-step:

### 1. Simplifying the Equation

First, we need to simplify the equation by combining like terms. To do this, we will subtract 'a' from both sides of the equation:

- (a + 28) - a = 2a - a
- This simplifies to
**28 = a**

### 2. Solution

Therefore, the solution to the equation (a + 28) = 2a is **a = 28**.

### Verification

To verify our solution, we can substitute the value of 'a' back into the original equation:

- (28 + 28) = 2 * 28
- 56 = 56

Since both sides of the equation are equal, our solution **a = 28** is correct.

### Conclusion

By simplifying the equation and isolating the variable 'a', we have successfully solved the equation (a + 28) = 2a, finding the solution to be **a = 28**.